2017
DOI: 10.5194/hess-2016-620
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impacts of spatial resolution and representation of flow connectivity on large-scale simulation of floods

Abstract: Global-scale River Models (GRMs) are core tools for providing consistent estimates of global flood hazard, especially in data-scarce regions. Due to former limitations in computational power and input datasets, most GRMs have been developed to use simplified representation of flow physics and run at coarse spatial resolutions. With increasing computational power and improved datasets, the application of GRMs to finer resolutions is becoming a reality. To support 15 development in this direction, the suitabilit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…An alternative to removing the channel is to estimate its dimensions empirically given observations from surveyed rivers using downstream hydraulic geometry theory, as demonstrated in the GFM of Yamazaki et al. (2013) and many regional models (Fleischmann et al., 2019; Grimaldi et al., 2019; Mateo et al., 2017; Neal et al., 2012; Paiva et al., 2011; Sayama et al., 2017; Schumann et al., 2013). Downstream hydraulic geometry theory aims to estimate how the width and depth of the channel are related to bank full discharge by a series of power laws (Leopold & Maddock, 1953).…”
Section: Methods For Defining River Channels In Data Sparse Flood Inu...mentioning
confidence: 99%
“…An alternative to removing the channel is to estimate its dimensions empirically given observations from surveyed rivers using downstream hydraulic geometry theory, as demonstrated in the GFM of Yamazaki et al. (2013) and many regional models (Fleischmann et al., 2019; Grimaldi et al., 2019; Mateo et al., 2017; Neal et al., 2012; Paiva et al., 2011; Sayama et al., 2017; Schumann et al., 2013). Downstream hydraulic geometry theory aims to estimate how the width and depth of the channel are related to bank full discharge by a series of power laws (Leopold & Maddock, 1953).…”
Section: Methods For Defining River Channels In Data Sparse Flood Inu...mentioning
confidence: 99%
“…Several studies have demonstrated the benefit of increasing the spatial resolution in macroscale RRMs. For example, Mateo et al (2017) showed that the river connectivity is better described at high spatial resolution, which improves the representation of the river flow dynamics within the river network. Nguyen-Quang et al (2018) concluded that high streamflow simulation performance requires a precise river catchment description, along with accurate forcing data (namely precipitation).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, GHMs usually performed worse in simulating hydrological extremes than normal values in some river basins. Possible reasons include the inadequate mathematical representation of hydrological systems (despite including some human impact parameterizations), limited availability and coarse spatial‐temporal resolution of global forcing data, and insufficient calibrations conducted in a few basins (Bierkens, 2015; W. B. Liu, Lim et al., 2018; Mateo et al., 2017; Veldkamp et al., 2018; Yang et al., 2019; Zaherpour et al., 2018).…”
Section: Introductionmentioning
confidence: 99%